Legal Protection for Intellectual Property Rights Holders Utilized as Debt Collateral: An Analysis of the Execution Norm Vacuum in Guarantees - Putu Krisna Indira Yasana Putri; Ni Luh Gede Astariyani (International Journal of Business, Law, and Education, 2026)
This article examines a regulatory disjunction in Indonesia: intellectual property rights (IPR) are formally recognized as fiduciary collateral, yet the legal framework remains incomplete at the enforcement stage. Using normative legal research with statutory, conceptual, and analytical approaches, the study evaluates primary, secondary, and tertiary legal materials through qualitative, descriptive, and prescriptive analysis. The findings show that IPR has a valid de jure status as collateral but remains practically subordinate because the law does not clearly regulate the object and method of realization, post-sale registration, accredited valuation, or the relationship between transferred economic rights and inalienable moral rights. These deficiencies weaken legal certainty for creditors and debtors. The article proposes an integrated framework consisting of IPR-specific enforcement procedures, standardized valuation, interoperable digital registries, contractual protection of moral rights, adaptive liquidation mechanisms, insurance and escrow arrangements, and specialized judicial oversight with proportional realization. Reform of the Fiduciary Guarantee Law and its implementing regulations is necessary to convert formal recognition into an enforceable and balanced secured-financing regime.